2013
DOI: 10.1590/s0100-39842013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Papel da ranitidina como meio de aprimorar a qualidade do exame de colangiopancreatografia por ressonância magnética

Abstract: Objective: To assess the impact of oral ranitidine on the imaging quality in magnetic resonance cholangiopancreatography (MRCP). Materials and Methods: Thirty-two patients underwent MRCP with 3D and 2D acquisitions, and three strategies for suppression of the gastrointestinal fluid signal: a) only at fasting; b) 12 hours after ingestion of 300 mg ranitidine; c) after oral administration of gadolinium solution. Three observers reviewed the images with a focus on the degree of visualization of the biliopancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, Torres et al in their trial concluded that the image quality obtained with ranitidine was similar to those obtained with only fasting and that negative oral contrast (gadolinium solution) was superior in comparison to ranitidine. 2 11…”
Section: Discussionmentioning
confidence: 99%
“…However, Torres et al in their trial concluded that the image quality obtained with ranitidine was similar to those obtained with only fasting and that negative oral contrast (gadolinium solution) was superior in comparison to ranitidine. 2 11…”
Section: Discussionmentioning
confidence: 99%